Bioenergy productivity of sugar beet irrigated with reclaimed wastewaters - Campi, Pasquale; Navarro, Alejandra; Palumbo, A. Domenico; Mastrangelo, Marcello; Lonigro, Antonio; Mastrorilli, Marcello (Italian Journal of Agronomy, 2015)
The use of treated wastewater to irrigate the sugar beet (Beta Vulgaris L. var. saccharifera) for bioethanol could play a strategic role to contrast the use of natural water resources and increase the productivity of the crop. The 2-year experiment (2013-2014) was performed on sugar beet irrigated with fresh water and wastewater at different steps of the reclamation process (secondary and tertiary treatments). The data obtained showed that the root sugar beet yield and ethanol production under fresh water treatment (52.2 Mg ha–1 and 5446 L ha–1) were lower respect to that obtained from the secondary and tertiary wastewater treatments (66.7 Mg ha–1 and 6785 L ha–1, and 58.7 Mg h–1 and 6164 L ha–1, respectively), with the same irrigation volumes. These results can depend on the higher quantity of nutrient uptake when wastewater is used for irrigation. In particular, the average N applied (as nitrate and ammonium) with irrigation during the growing seasons (2013 and 2014) was corresponding to the supply of 4, 28 and 20 kg ha–1, for the fresh water, secondary, and tertiary wastewater treatments, respectively.